Sociologia contemporanea, teoria critica, teoria sociale: il contributo di Boltanski. Una rilettura critica - Lo Schiavo, Lidia (SocietàMutamentoPolitica, 2021)
In contemporary sociological theory, the work of Boltanski and his research group is viewed as central, for at least two reasons: its contribution to reopening debate in critical social theory and renewing the European sociological tradition. This paper sets out to analyse the main theoretical-conceptual elements of his “pragmatic sociology of critique” and explores the critical debate that followed it.